A “Festa da diversidade” em Cruz Alta - RS como território de exercício da sexualidade LGBT e de seu reconhecimento social - Forno, Leandro Rosa Dal (2013)
This work is the result of intensive research in the field of geography that presents important reflections on theoretical / methodological concepts this science and other sciences. And understand the materialization of activities of social recognition of groups LGBT‟s - Lesbian, Gay, Bisexual and Transgender - especially the emergence of political and cultural events, it becomes the main focus of this research. Initially, the work presents narratives of life stories of individuals who make up the LGBT social movement in the city of Cruz Alta-RS, which are indispensable for understanding the construction of a network of friendship that resulted in the production of tactics and strategies to recognition and exercise of sexuality. The paper aims to present a methodology based on the positionality of the researcher, as it stands as researched. Come here a new theoretical model already presented by Geographies Feminists and Queers who observe a moment of rupture with traditional methodologies. Secondly, the paper presents the city of Cruz Alta-RS and its historical formation and identity, which directly influenced the formation of territoriality specific recognition groups LGBT's. Moreover, the work aims to present and redeem the emergence of LGBT movements in Brazil, and its importance to the deconstruction of a heteronormative society only. At this time, we also feature local movement LGBT, which is a result of a number of factors that promoted the creation of the Party of Diversity, the main object of this research. And finally, the work seeks to understand the importance of social networks and virtual materials in the execution of the event, and the process of territorial relational and locational plots produced from the Party Diversity, which put the city of Cruz Alta - RS as a territory of exercise and social recognition of sexualities LGBT‟s.